POLYMER BASED BIO-FILTERS - Research, Phd (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
To investigate and analysebloodÂ  and to separate various blood components like WBC, RBC, PLATELETS and PLASMA from the blood. We use MEMS for this process as it requires only small samples of volume. Polymers do not show any interaction with biological fluids and they are cost effective and easy to fabricate. Polymers are more transparent, so easy to observe the process. The fabrication process is simpler and more cost effective than the onventional process which is lengthy and timely repeated process.